Reconhecimento de sentenças no silêncio e no ruído, em campo livre, em indivíduos portadores de perda auditiva neurossensorial de grau moderado - Padilha, Cristiane Bertolazi (2008)
In the clinical routine of an audiologist, it is becoming more frequent the complaints about speech misunderstanding in a noisy environment. Audiological tests which use sentences as stimulus have been object of research because, besides examining the real auditory skill of the patient, they promote a direct approximation to communicative situations and provide information that will indicate the most adequate behavior to be recommended to the patient with hearing deficits. The aim of this study was to determine sentences recognition thresholds in free field, with the presence and the absence of competitive noise, in a group of participants with neurossensorial hearing loss of a moderate level. It was examined 50 participants, 27 men and 23 women, aged between 45 and 76. Firstly, it was carried out anamnesis, meatuscopy, threshold tonal audiometry, SRT and SRPI tests. Next, using the Portuguese Sentences Lists test (PSL, 1998), SRTQ and SRTN tests were carried out, with a fixed noise level of 65 dB A. The average SRTQ was 60,90 dB A, the average SRTN in the same group was 68,20 dB A and the average S/N ratio was + 3,20 dB A. The inclusion of tests in free field using sentences as stimulus, with and without competitive noise, after the basic audiological evaluation in a patient with hearing deficits, have brought answers broader than the skills to detect the presence of pure tones and to recognize isolated words. These tests assess the patient as a whole, simulating communicative situations as well as providing data about skills and limitations of each person which determine his/her communication capacity.